2017
DOI: 10.1111/acel.12568
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength mediates the relationship between mitochondrial energetics and walking performance

Abstract: SummarySkeletal muscle mitochondrial oxidative capacity declines with age and negatively affects walking performance, but the mechanism for this association is not fully clear. We tested the hypothesis that impaired oxidative capacity affects muscle performance and, through this mechanism, has a negative effect on walking speed. Muscle mitochondrial oxidative capacity was measured by in vivo phosphorus magnetic resonance spectroscopy as the postexercise phosphocreatine resynthesis rate, kPC r, in 326 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
85
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 42 publications
12
85
1
Order By: Relevance
“…In accordance with this hypothesis, we have recently shown that muscle mitochondrial capacity is a strong independent correlate of lower extremity performance, especially in tasks that require walking at fast speeds or for long distances, and that long‐term exposure to some adiposity‐related factors may adversely affect mitochondrial function in humans . We have also found that muscle strength significantly mediates the relationship of mitochondrial function with walking performance . Overall, these results indicate that oxidative phosphorylation is progressively impaired with ageing; it is unclear whether this is because the number of mitochondria per muscle volume is diminished, the intrinsic capacity of mitochondria to generate ATP is impaired, or the availability of oxygen and nutrients at different levels of effort is compromised.…”
Section: Mitochondrial Oxidative Capacity and Metabolic Flexibilitysupporting
confidence: 57%
See 1 more Smart Citation
“…In accordance with this hypothesis, we have recently shown that muscle mitochondrial capacity is a strong independent correlate of lower extremity performance, especially in tasks that require walking at fast speeds or for long distances, and that long‐term exposure to some adiposity‐related factors may adversely affect mitochondrial function in humans . We have also found that muscle strength significantly mediates the relationship of mitochondrial function with walking performance . Overall, these results indicate that oxidative phosphorylation is progressively impaired with ageing; it is unclear whether this is because the number of mitochondria per muscle volume is diminished, the intrinsic capacity of mitochondria to generate ATP is impaired, or the availability of oxygen and nutrients at different levels of effort is compromised.…”
Section: Mitochondrial Oxidative Capacity and Metabolic Flexibilitysupporting
confidence: 57%
“…Multiple distinct and pre‐packaged adaptive strategies and signalling pathways in muscle allow boosting of energy production when demand increases, such as during prolonged exercise . For example, studies in human and animal models have revealed that the ability for the mitochondrial electron transport system to respond to increased demand declines with ageing, and this may account for some of the observed decrease in fitness in older persons .…”
Section: Mitochondrial Oxidative Capacity and Metabolic Flexibilitymentioning
confidence: 99%
“…While this is expected, it raises questions about the clinical relevance of these findings. We have previously reported, using data from this cohort, that k PCR was strongly associated with 400‐meter walking speed,30 which suggests that even such variations in this normal range might underlie subclinical alterations in function. We are in the process of collecting longitudinal data of ABI, mitochondrial function, and walking endurance from a larger sample, which will allow further elaboration on these findings.…”
Section: Discussionmentioning
confidence: 80%
“…We have previously reported, using data from the same cohort, that reduced mitochondrial energy production was associated with less exercise endurance, assessed by 400‐meter walking speed 30. Future studies are needed to demonstrate whether modest reduction of ABI when associated with impaired mitochondrial function predicts the risk of developing overt PAD.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it is reported that the step -up training is advantageous for increasing the strength of the knee extensor muscles (Kim, 2015). In addition, increased knee extensor muscular strength is closely related to the improvement of walking speed (Zane et al, 2017).…”
Section: ⅳ Discussionmentioning
confidence: 99%